2015
DOI: 10.1186/s13023-015-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pemphigus and pemphigoid autoantibodies in the general population

Abstract: BackgroundMucocutaneous blistering is characteristic of autoimmune bullous dermatoses (AIBD). Blisters are caused by autoantibodies directed against structural components of the skin. Hence, detection of specific autoantibodies has become a hallmark for AIBD diagnosis. Studies on prevalence of AIBD autoantibodies in healthy individuals yielded contradictory results.MethodsTo clarify this, samples from 7063 blood donors were tested for presence of anti-BP180-NC16A, anti-BP230 and anti-Dsg1/3 IgG by indirect imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 44 publications
3
34
2
2
Order By: Relevance
“…Despite the fact that MS, of all neurologic diseases, has the strongest association with BP (Lai et al, 2016), the existence of autoantibodies against BP180 in patients with MS has so far been analyzed by only one study, in which none of the MS sera tested (n ¼ 50) showed positivity in the BP180-NC16A ELISA or in the immunoblotting against the full-length BP180 (Recke et al, 2016). We found that about half of MS sera recognize the full-length BP180 in immunoblotting, but the proportion that showed elevated antieBP180-NC16A ELISA values was only slightly higher than in the control group and similar to that reported in general population (Prussmann et al, 2015;Wieland et al, 2010). The obvious explanation for why our results differed from those described is the sensitivity of the immunoblotting assay, because we used recombinant BP180 while the previous study employed a keratinocyte extracellular matrix.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the fact that MS, of all neurologic diseases, has the strongest association with BP (Lai et al, 2016), the existence of autoantibodies against BP180 in patients with MS has so far been analyzed by only one study, in which none of the MS sera tested (n ¼ 50) showed positivity in the BP180-NC16A ELISA or in the immunoblotting against the full-length BP180 (Recke et al, 2016). We found that about half of MS sera recognize the full-length BP180 in immunoblotting, but the proportion that showed elevated antieBP180-NC16A ELISA values was only slightly higher than in the control group and similar to that reported in general population (Prussmann et al, 2015;Wieland et al, 2010). The obvious explanation for why our results differed from those described is the sensitivity of the immunoblotting assay, because we used recombinant BP180 while the previous study employed a keratinocyte extracellular matrix.…”
Section: Discussionsupporting
confidence: 84%
“…However, the prevalence of these antibodies has varied in relation to the sensitivity and specificity of the assay used and the control group. The lowest prevalence has been less than 1% in a large cohort of blood donors of unknown ages, 54 other publications have given values of 7.5%, 55 13%, 16% and 26% for ELISA and or immunoblots 56 although higher values have been reported. 57 Results for IIF have generally shown o5% positivity 55,56 although this was 19% (n = 32) in another study.…”
Section: Pathogenesismentioning
confidence: 90%
“…In our study population, in addition to antibodies against BP180, BP230 and COL7, antibodies against DSG1 and DSG3 were evaluated. These proteins are members of the cadherin cell adhesion molecule superfamily and are major components of the cell–cell junctions that help resist shearing forces and are found in high concentrations in cells subject to mechanical stress [14]. The pathogenic role of these antibodies has previously been shown in experimental animals and in humans.…”
Section: Discussionmentioning
confidence: 99%